2010
DOI: 10.1186/1477-7525-8-25
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the psychosocial health of adolescent and young adult (AYA) cancer survivors: a critical review

Abstract: BackgroundAdolescent and young adult (AYA) cancer survivors require psychometrically rigorous measures to assess their psychosocial well-being. Without methodologically adequate scales the accuracy of information obtained on the prevalence of needs, predictors of risk, and the potential success of any interventions, can be questioned. This review assessed the psychometric properties of measures designed specifically to identify the psychosocial health of this unique population.MethodsMedline, PsycINFO, CINAHL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 58 publications
(72 reference statements)
1
72
0
1
Order By: Relevance
“…It is recommended that future studies focus on establishing psychometric properties of the measure. Key psychometric properties for exploration include an examination of construct validity, which could be examined via factor analysis and known-groups comparisons [50][51][52]. The internal consistency of factors identified through factor analysis could be explored, and test-re-test reliability should also be examined [50][51][52].…”
Section: Limitationsmentioning
confidence: 99%
“…It is recommended that future studies focus on establishing psychometric properties of the measure. Key psychometric properties for exploration include an examination of construct validity, which could be examined via factor analysis and known-groups comparisons [50][51][52]. The internal consistency of factors identified through factor analysis could be explored, and test-re-test reliability should also be examined [50][51][52].…”
Section: Limitationsmentioning
confidence: 99%
“…19 It is important to note that previous studies of HRQOL in YASCC largely relied on quantitative data collected by existing instruments. 21,22 Theoretically, quantitative methods are useful for comparing HRQOL across subgroups of cancer survivors given the established framework or instruments with pre-specified domains of HRQOL (e.g., physical, psychological, and social functioning). 21,22 In contrast, qualitative methods allow for a more thorough exploration of the unique HRQOL issues for YASCC that have traditionally been neglected in quantitative instruments.…”
mentioning
confidence: 99%
“…21,22 Theoretically, quantitative methods are useful for comparing HRQOL across subgroups of cancer survivors given the established framework or instruments with pre-specified domains of HRQOL (e.g., physical, psychological, and social functioning). 21,22 In contrast, qualitative methods allow for a more thorough exploration of the unique HRQOL issues for YASCC that have traditionally been neglected in quantitative instruments. In other words, qualitative methods may facilitate a greater understanding of HRQOL for this population by allowing the researcher to identify and explore the domains of HRQOL that are relevant to this population.…”
mentioning
confidence: 99%
“…4 In psychosocial research, the majority of patient-reported outcome instruments have been validated either for children < 18 years of age or for adults 18 years of age or older; very few span both age groups, although research to address this deficit is ongoing. 19,20 As initial steps toward the goal of collecting prospective psychosocial data on AYAs, LIVESTRONG supported two initiatives: (1) NCI's Adolescent and Young Adult Health Outcomes and Patient Experience (AYA HOPE) study, a population-based analysis that determined best practices for medical record collection, validated the feasibility of assessing psychosocial outcomes in recent survivors of AYA cancer, [21][22][23] and reported on the social information and service needs, health-related quality of life, work disparities, and educational disparities of AYAs with cancer [24][25][26] and (2) the Alliance's AYA cohort study, a prospective, multi-institutional study testing the feasibility of collecting AYAs' clinical, psychosocial, and health-related qualify of life data at several time points during the first year of cancer therapy. 4 The Alliance made strides toward coordinating the research and clinical efforts of the pediatric and adult branches of NCI-designated cancer centers through the formation and coordination of the Cancer Centers Working Group (CCWG).…”
Section: Research and Tool Developmentmentioning
confidence: 99%